Work songs: music, art and culture, aligned in a tradition that resists the times (Research, Society and Development, 2022)
This article aimed to develop a qualitative analytical study on three work singing groups, focusing on their singing, their stories and the environment where these workers sing. In this direction, the following movements were carried out: to discuss the representation of these songs taking as a guide the life and art of the Destaladeiras de Fumo de Arapiraca, Catadoras do coco babaçu and groups of Baita do Feijo. The research was designed from a qualitative perspective, in line with cultural studies, having as main methodological resources, interviews and document analysis. As main theoretical references, authors who help the understanding of concepts such as Fonseca, Mattar, Hanburger, among others mentioned later, were taken as the main theoretical references. From this research, it is understood that the relationship between the work singing groups represents an inseparable link between popular culture and communities, creating a bridge in which the transit of different knowledge is possible, bringing connected experiences between art, music and culture.